2018
DOI: 10.1097/inf.0000000000001882
|View full text |Cite
|
Sign up to set email alerts
|

Nephrotoxicity With Vancomycin in the Pediatric Population

Abstract: Though the rate of vancomycin-induced nephrotoxicity is increased in pediatric patients with higher vancomycin troughs, other factors such as intensive care unit admission, hypovolemia and concurrent nephrotoxic drug use appear to contribute to the development of nephrotoxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
42
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 37 publications
5
42
0
4
Order By: Relevance
“…Recently, a revised consensus guideline developed by different scientific associations has been published, recommending a target of an AUC/MIC ratio of 400 to 600 (assuming a MIC of 1 mg/L) for empiric dosing in both adult and pediatric patients to maximize clinical efficacy and minimize nephrotoxicity [ 5 ]. However, there is a lack of evidence for this parameter in children due to the complexity of vancomycin clearance in the various pediatric age groups, and the differences in tissue site-of-infection drug exposure as a consequence of higher pharmacokinetic variability [ 5 , 6 ]. Due to the impracticalities of calculating the AUC, target trough concentrations of 15 to 20 mg/L are used as a surrogate marker in adults with normal renal function when MIC is ≤1 mg/mL [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a revised consensus guideline developed by different scientific associations has been published, recommending a target of an AUC/MIC ratio of 400 to 600 (assuming a MIC of 1 mg/L) for empiric dosing in both adult and pediatric patients to maximize clinical efficacy and minimize nephrotoxicity [ 5 ]. However, there is a lack of evidence for this parameter in children due to the complexity of vancomycin clearance in the various pediatric age groups, and the differences in tissue site-of-infection drug exposure as a consequence of higher pharmacokinetic variability [ 5 , 6 ]. Due to the impracticalities of calculating the AUC, target trough concentrations of 15 to 20 mg/L are used as a surrogate marker in adults with normal renal function when MIC is ≤1 mg/mL [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…When compared to adults, achieving therapeutic serum vancomycin concentrations (SVCs) with IIV in children requires higher doses and shorter intervals given their increased renal clearance [ 9 , 13 ]. However, higher doses have also been associated with increased nephrotoxicity in pediatrics [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nephrotoxicity is often defined as an increase in serum creatinine of >50% from baseline . Factors that are associated with nephrotoxicity in adults and children are vancomycin trough concentrations over 15 mg/L and concomitant use of nephrotoxic medications …”
Section: Introductionmentioning
confidence: 99%
“…The strongest level of evidence in children is the association of acute kidney injury with higher vancomycin exposure, especially with troughs exceeding 15 to 20 mg/L. 6 In addition, one pediatric study found an AUC exposure of greater than 800 mg × h/L over 24 hours was strongly associated with risk for acute kidney injury. 7 These findings suggest that high vancomycin exposure correlates with nephrotoxicity, so with AUC monitoring, the goal exposure should be less than 800 mg × hr/L over 24 hours.…”
Section: Key Recommendations For Pediatric Hospitalistsmentioning
confidence: 99%